The Direct Detection and Kinetic Studies of Dimethylgermylene and Tetramethyldigermene In Solution By Nanosecond Laser Flash Photolysis - Lollmahomed, Farahnaz Begum (My University, 2009)
Dimethylgermylene (GeMe2) has been generated by laser flash photolysis of 1,1dimethyl-3-phenylgermacyclopent-3-ene (23) and 1,1,3-trimethyl-4phenylgermacyclopent-3-ene (24) in hexanes at 25°C and its absorption maximum (λmax) has been unambiguously established to be 470 nm. GeMe2 decays with second-order kinetics under these conditions (2k/ε. = (10 ± 2) x 10^7 cm s^(-1)) to give Ge2Me4 (λmax = 370 nm). Kinetic studies of the reactions of GeMe2 and Ge2Me4 with typical germylene/digermene scavengers such as 1,3-dienes, olefins, alkynes, alkyl halides, group 14 metal hydrides, carboxylic acids, and amines have been carried out.
GeMe2 reacts reversibly with MeOH, t-BuOH and THF to form Lewis acid-base complexes which exhibit relatively strong absorption bands that are blue-shifted with respect to GeMe2 (λmax ~ 295-310 nm). The decay of the Me2Ge-MeOH complex is accelerated in the presence of a Brnnsted acid (acetic acid or methanesulfonic acid) or base (MeONa). The reactions of the Me2Ge-THF complex with sodium methoxide, methanesulfonic acid, 4,4-dimethyl-1-pentene, 2,3-dimethyl-1-butadiene, acetic acid and CC4 have also been studied in THF.
The photochemistry of two well-known precursors to GeMe2, namely dodecamethylcyclohexagermane (14) and dimethylphenyl(trimethylsilyl)germane (18) was reinvestigated. Laser flash photolysis of 14 in hexanes led to the formation of two transients, one with λmax= 490 nm (τ < & = 10 ns) and the second with λmax= 470 nm. The latter decays with second-order kinetics with concomitant formation of a new transient with λmax= 370 nm. The transient at 470 nm is assigned to GeMe2 and that at 370 nm to Ge2Me4, based on comparisons to the results obtained from laser flash photolysis of 23 and 24. Laser flash photolysis of 18-in hexane gives rise to two absorption bands centered at λmax = 300 nm and λmax = 430 nm, which are assigned to the dimethylphenylgerrnyl radical and the conjugated gerrnene derivative 38, respectively. GeMe2 cannot be detected in laser flash photolysis experiments with this compound.
Dimethylgermylene and Tetramethyldigermene In Solution
Keywords: Dimethylgermylene, GeMe2, photolysis, 1, 1-dimethyl-3-phenylgermacyclopent-3-ene, 1,1,3-trimenthyl-4-phenylgermacyclopent-3-ene, MeOH, t-BuOH, THF, lewis acid-base complexes, Bronsted acid, acetic acid, methanesulfonic acid